Learning a Spatial Task by Trial and Error in Drosophila. - Stern, U.; Srivastava, H.; Chen, H.L.; Mohammad, F.; Claridge-Chang, A.; Yang, C.H. (Current Biology, 2019)
The ability to use memory to return to specific locations for foraging is advantageous for survival. Although recent reports have demonstrated that the fruit flies Drosophila melanogaster are capable of visual cue-driven place learning and idiothetic path integration [1-4], the depth and flexibility of Drosophila's ability to solve spatial tasks and the underlying neural substrate and genetic basis have not been extensively explored. Here, we show that Drosophila can remember a reward-baited location through reinforcement learning and do so quickly and without requiring vision. After gaining genetic access to neurons (through 0273-GAL4) with properties reminiscent of the vertebrate medial forebrain bundle (MFB) and developing a high-throughput closed-loop stimulation system, we found that both sighted and blind flies can learn-by trial and error-to repeatedly return to an unmarked location (in a rectangularly shaped arena) where a brief stimulation of the 0273-GAL4 neurons was available for each visit. We found that optogenetic stimulation of these neurons enabled learning by employing both a cholinergic pathway that promoted self-stimulation and a dopaminergic pathway that likely promoted association of relevant cues with reward. Lastly, inhibiting activities of specific neurons time-locked with stimulation of 0273-GAL4 neurons showed that mushroom bodies (MB) and central complex (CX) both play a role in promoting learning of our task. Our work uncovered new depth in flies' ability to learn a spatial task and established an assay with a level of throughput that permits a systematic genetic interrogation of flies' ability to learn spatial tasks.